Analisis Efektivitas Penatausahaan Barang Milik Negara Melalui Aplikasi SIMAK-BMN - Nurussyifa Razak; Juliana Nasution (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2022)
This study aims to observe the effectiveness of the administration of State Property through the SIMAK-BMN Application Case Study at the Regional Office of the National Land Agency of North Sumatra Province. The location of the research was carried out at the Regional Office of the National Land Agency of North Sumatra Province which is located at Jl. Brigadier General Katamso No. 45, AUR, Medan City, North Sumatra. The problem raised in this study is the existence of software constraints in the BMN input process through SIMAK-BMN. This study uses qualitative research methods, to describe or analyze a research result. The results of this study indicate that the lack of effectiveness in the SIMAK-BMN application, the occurrence of program errors in the application, so that the BMN manager users experience problems so they need to repeat the data input process from the beginning. So it is necessary to make improvements to the SIMAK-BMN application software which is better so that the BMN data input process is more effective